Catalytic pyrolysis of cow manure over a Ni/SiO2 catalyst using CO2 as a reaction medium. (15th March 2020) - Lee, Dong-Jun; Jung, Sungyup; Jeong, Kwang-Hwa; Lee, Dong-Hyun; Lee, Sung-Hyoun; Park, Young-Kwon; Kwon, Eilhann E.
Abstract: The massive production of manures in the livestock industry gives rise to detrimental effects on rural environment due to the contamination of soil and streams from the disposed manure. This study directly utilizes an animal manure as a source for syngas production so that it can be used as energy or fuel instead of being discarded. Cow manure (CM) was employed as the feedstock for syngas generation via thermo-chemical process in the CO2 environment. In addition, the mechanistic roles of CO2 in CM pyrolysis were examined. It was found that H2 and CO gases were formed via dehydrogenation and deoxygenation at ≤ 500 °C in both CO2 and N2 conditions, while CO2 expedited the substantial generation of CO at ≥ 600 °C via the homogeneous reaction of volatile organic compounds (VOCs). CO2 was less likely to affect the homogeneous reaction with VOCs at ≤ 500 °C, but it was effective synergistically with a Ni/SiO2 catalyst in the temperature range. CO2 -cofeeding catalytic pyrolysis of CM showed 25% more gas formation than CM catalytic pyrolysis in the N2 condition. Therefore, this sustainable approach suggests the feasibility of the establishment of a CM-to-energy platform for syngas generation in the presence of greenhouse gas. Highlights: Cow manure was utilized as a source for syngas formation instead of being disposed. For more sustainable conversion of cow manure, CO2 was used as a co-feed reactant. CO2 expedited thermal cracking and homogeneous reaction of VOCs at ≥ 600 °C. CO2 and Ni/SiO2 catalyst synergistically promoted syngas formation at ≤ 500 °C.